The Relation Between Anxiety and Nurses’ Performance at Atma Husada Mahakam Hospital, Samarinda - Mukhripah Damaiyanti (Universitas Muhammadiyah Kalimantan Timur, 2019)
Nurses working at the Mental Hospital are different from other section nurses, there are loads of nurses possessed anxieties when they treat mental patients and it disrupts their performance. Whereas, the nurse performance has a vital and strategic value that depicts the quality of service in the hospital. Baring that in mind, this study aims to determine the relationship of anxiety of nurses toward their performances of treating patients at Atma Husada Mahakam Mental Hospital, Samarinda. Using the Lameshow formula, this study obtains a sample size of 96 people. The sampling technique used is Stratified Random Sampling. This study data retrieval is in September - October 2017. The questionnaire used is The Six Dimension Scale of Nursing Performance (SDNS and Hamilton Anxiety Rating Scale (HAM-A). Bivariate analysis conducted uses the Pearson Product Moment with a p-value of 0,000 with the correlation value of anxiety on nurse performance in the frequency of nurses 'activities r = 0.41 and the quality of nurses' activities r = 0.54 which means that it correlates strongly. There must be some effort to minimize anxiety mental nurses by using a new innovation and training to increase nurses knowledge, abilities and skills so it can improve performance of nurses in carrying out nursing care and action.